Archaeological Geology of the World's First Emerald Mine - Harrell, James (Geoscience Canada, 2004)
ABSTRACT Emerald, a green transparent variety of beryl, was one of the most highly prized gemstones in antiquity. The earliest known emerald mine is located in the mountain valley of Wadi Sikait in Egypt's Eastern Desert, where mining probably began toward the end of the Ptolemaic period in the first century BC. Most of the mining activity, however, dates to the Roman and Byzantine periods, from the late first century BC through the sixth century AD. The Romans referred to emerald as smaragdus and named the Sikait region Mons Smaragdus or Emerald Mountain. An archaeological geology survey of Wadi Sikait was undertaken for the purpose of mapping the distribution of ancient mine workings, deducing the ancient mining methods, and describing the geological occurrence of emerald. It was found that emerald and other green beryls occur within the contact zone between phlogopite schist and intrusive quartz and pegmatite veins. The workings, which were excavated in the softer phlogopite schist with flat-edged chisels and pointed picks, are mostly shallow, open-cut trenches that follow the quartz/ pegmatite veins. Some workings continue as much as 100 m underground and are still largely unexplored. It is noteworthy that the geological occur-rence of beryl in Wadi Sikait, the world's oldest emerald mine, is essentially the same as for the world's newest emerald discovery at Regal Ridge in Canada's Yukon Territory.